2002
DOI: 10.1017/s1352465802003119
|View full text |Cite
|
Sign up to set email alerts
|

Can a “Relapse Prevention” Module Facilitate the Transfer of Training?

Abstract: The objective of this pilot study was to evaluate the relative effectiveness of two approaches to staff training. Multidisciplinary mental health staff, receiving a standard training programme (N = 45), were compared on multiple measures with an experimental group (N = 11), receiving a programme featuring a ''relapse prevention'' module. This module was designed to improve the transfer of the training. The staff receiving the relapse prevention module reported significantly greater generalization of the traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Three of the 5 group comparison studies included random assignment. Five of the 10 studies included a follow-up assessment, which varied in duration from 2 (Milne, Westerman, & Hanner, 2002) to 12 months (Kelly et al, 2000). Studies examined a variety of assessment domains (e.g., knowledge, attitudes, practice, satisfaction) by means of behavior observation and predominantly non-standardized, self-report methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the 5 group comparison studies included random assignment. Five of the 10 studies included a follow-up assessment, which varied in duration from 2 (Milne, Westerman, & Hanner, 2002) to 12 months (Kelly et al, 2000). Studies examined a variety of assessment domains (e.g., knowledge, attitudes, practice, satisfaction) by means of behavior observation and predominantly non-standardized, self-report methods.…”
Section: Resultsmentioning
confidence: 99%
“…Parsons and Reid (Type 2, 1995) found that supervisor feedback enhanced maintenance of staff members’ teaching skills. Milne, Westerman, and Hanner (Type 2, 2002) examined the utility of a relapse prevention module and found that in comparison to a group receiving standard training, the relapse prevention group demonstrated greater knowledge and generalization of training across behaviors and clients.…”
Section: Resultsmentioning
confidence: 99%
“…Given that participants also identified common misconceptions about SFBT as a barrier to use, it may also be worth considering explicitly including information on these topics within training. This could perhaps form part of a 'relapse' prevention section to the course, similar to that described by Milne, Westerman, and Hanner (2002).…”
Section: Theme 1: 'Transferring Techniques Is Hard Without Practice Amentioning
confidence: 99%
“…The ex-trainee role in the post-training environment has also been shown to be a relevant predictor of the effectiveness of TD&E (e.g. Burke, 1997;Gist, Stevens & Bavetta, 1991;Hutchins & Burke, 2006;Latham & Heslin, 2003;Milne, Westerman & Hanner, 2002;Morin & Latham, 2000;Richman-Hirsch, 2001;Stevens & Gist, 1997;Wexley & Baldwin, 1986). A model of relapse prevention (Marx, 1982) may greatly help to describe the ex-trainees as promoters of the application of learning after training, who can develop strategies to apply, at work, what they have learned during training (Pilati & Borges-Andrade, 2005).…”
Section: Antecedents Of Effectiveness Of Training On Workmentioning
confidence: 99%